Cyberbullying and self-esteem in Australian adults - Kerryn Brack; Nerina Caltabiano (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2014)
Cyberbullying research is currently focused on identifying personal factors which increase the risk of an individual being involved in the behaviour. Recent findings indicate that within the web of cyberbullying culture a large group of individuals are both cyberbullies and victims. This group of cyberbully/victims has been shown to differ from pure cyberbullies or victims on various factors during adolescence; particularly self-esteem. However, little research to date has investigated cyberbullying behaviour in adults. The current study examined the prevalence of cyberbully typologies and their relationship with self-esteem within a convenience sample of 164 Australian young adults (72% being females; 17-25 years). Results found that the largest group identified were cyberbully/victims (62%), followed by individuals not involved (17%), cyberbullies (11%) and cybervictims (10%) respectively. The ratio of males and females in each of the four cyberbully typologies was similar. Contrary to previous research, all four cyberbully typologies reported similar levels of self-esteem. These findings suggest that research should examine cyberbullying behaviour across all age groups to determine if this is related to different factors in adolescence compared to adulthood. Limitations and future recommendations are discussed.